Biosynthesis of micro‐ and nanocrystals of Pb (II), Hg (II) and Cd (II) sulfides in four Candida species: a comparative study of in vivo and in vitro approaches. Issue 2 (16th January 2017) - Cuéllar‐Cruz, Mayra; Lucio‐Hernández, Daniela; Martínez‐Ángeles, Isabel; Demitri, Nicola; Polentarutti, Maurizio; Rosales‐Hoz, María J.; Moreno, Abel
Summary: Nature produces biominerals (biogenic minerals) that are synthesized as complex structures, in terms of their physicochemical properties. These biominerals are composed of minerals and biological macromolecules. They are produced by living organisms and are usually formed through a combination of chemical, biochemical and biophysical processes. Microorganisms like Candida in the presence of heavy metals can biomineralize those metals to form microcrystals (MCs) and nanocrystals (NCs). In this work, MCs and NCs of PbS, HgS or HgCl2 as well as CdS are synthesized both in vitro (gels) and in vivo by four Candida species. Our in vivo results show that, in the presence of Pb 2+, Candida cells are able to replicate and form extracellular PbS MCs, whereas in the presence of Hg 2+ and Cd 2+, they did synthesize intercellular MCs from HgS or HgCl2 and CdS NCs respectively. The MCs and NCs biologically obtained in Candida were compared with those PbS, HgS and CdS crystals synthetically obtained in vitro through the gel method (grown either in agarose or in sodium metasilicate hydrogels). This is, to our knowledge, the first time that the biosynthesis of the various MCs and NCs (presented in several species of Candida ) has been reported. This biosynthesis is differentially regulated in each of these pathogens, which allows them to adapt and survive in different physiological and environmental habitats. Abstract :